2017
DOI: 10.1530/eje-16-1044
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Endocannabinoids and metabolism: past, present and future

Abstract: The endocannabinoid system (ECS), including cannabinoid type 1 and type 2 receptors (CB 1 R and CB 2 R), endogenous ligands called endocannabinoids and their related enzymatic machinery, is known to have a role in the regulation of energy balance. Past information generated on the ECS, mainly focused on the involvement of this system in the central nervous system regulation of food intake, while at the same time clinical studies pointed out the therapeutic efficacy of brain penetrant CB 1 R antagonists like ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 145 publications
4
84
1
1
Order By: Relevance
“…The harmful psychiatric effects have been linked to the antagonizing effect of rimonabant on constitutively active CB1Rs in the ventral tegmental area, and in the amygdala (Meye et al, 2013). Before the clinical development was stopped, rimonabant showed promising effects to improve glycemic control and lessen cardiometabolic risk factors (Despres et al, 2005;Nissen et al, 2008;Van Gaal et al, 2008) Research continues to uncouple the metabolic benefits from the harmful events of CB1R targeting (Simon and Cota, 2017), providing hope that a new generation of safe and efficacious CB1R-based agonists might still be possible.…”
Section: Rimonabantmentioning
confidence: 99%
“…The harmful psychiatric effects have been linked to the antagonizing effect of rimonabant on constitutively active CB1Rs in the ventral tegmental area, and in the amygdala (Meye et al, 2013). Before the clinical development was stopped, rimonabant showed promising effects to improve glycemic control and lessen cardiometabolic risk factors (Despres et al, 2005;Nissen et al, 2008;Van Gaal et al, 2008) Research continues to uncouple the metabolic benefits from the harmful events of CB1R targeting (Simon and Cota, 2017), providing hope that a new generation of safe and efficacious CB1R-based agonists might still be possible.…”
Section: Rimonabantmentioning
confidence: 99%
“…we observed that the body weight values were not changed with fructose intake. It is known that THC has the regulatory effect on body weight and food intake . Recently, Brierley et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that THC has the regulatory effect on body weight and food intake. [24] Recently, Brierley et al [25] reported that purified cannabigerol from the cannabis plant is a novel appetite stimulant. However, Cluny et al [26] clarified that chronic THC administration reduced energy intake in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, rimonabant was withdrawn for treatment due to its adverse effects such as causing mood swings and suicide (Christensen et al 2007). Research is still ongoing for food intake regulation and it is proposed that peripherally restricted CB1 receptor blockers may be therapeutic in the future (Simon and Cota 2017). Moreover, the CB1 receptor was frequently the focus of research, with frequent recurrence of keywords: "CB1" (n = 6), "cannabinoid CB1 receptor" (n = 5), and anandamide (n = 17, citations per manuscript = 823.6), its famous agonist reported by the manuscript with the highest citation count (Devane et al 1992).…”
Section: Bubble Mapsmentioning
confidence: 99%